Inter-nucleosomal potentials from nucleosomal positioning data [research data]" - Li, Kunhe; Oiwa, Nestor Norio; Mishra, Sujeet Kumar; Heermann, Dieter W. (Universität, 2022)
This dataset accompanies the paper "Intra-chromosomal potentials from nucleosomal positioning data." In this paper, a systematic ​method to develop...
Gesehen am 30.03.2022
Keywords: Forschungsdaten; Datenbank